Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/00273171.2016.1215898
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Bifactor Analysis: The Schmid-Leiman Orthogonalization and Jennrich-Bentler Analytic Rotations

Abstract: Analytic bifactor rotations (Jennrich & Bentler, 2011, 2012) have been recently developed and made generally available, but are not well understood. The Jennrich-Bentler analytic bifactor rotations (bi-quartimin and bi-geomin) are an alternative to, and arguably an improvement upon, the less technically sophisticated Schmid-Leiman orthogonalization (Schmid & Leiman, 1957). We review the technical details that underlie the Schmid-Leiman and Jennrich-Bentler bifactor rotations, using simulated data structures to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 41 publications
3
92
0
2
Order By: Relevance
“…When more than one dimension was found in the exploratory factor analysis, we conducted an exploratory bifactor analysis, using the Schmid-Leiman orthogonalization (Schmid & Leiman, 1957). An explanation of the Schmid-Leiman procedure is provided in Mansolf and Reise (2016). For this exploratory analysis the Root Mean Square of Residuals (RMSR) and Kelley's criterion (Kelley, 1935) were used as fit indices.…”
Section: Factor Analysismentioning
confidence: 99%
“…When more than one dimension was found in the exploratory factor analysis, we conducted an exploratory bifactor analysis, using the Schmid-Leiman orthogonalization (Schmid & Leiman, 1957). An explanation of the Schmid-Leiman procedure is provided in Mansolf and Reise (2016). For this exploratory analysis the Root Mean Square of Residuals (RMSR) and Kelley's criterion (Kelley, 1935) were used as fit indices.…”
Section: Factor Analysismentioning
confidence: 99%
“…The bi-geomin rotation is recommended in cases where cross-loadings are likely to be present (e.g. Mansolf & Reise, 2016). Scaling and identification were achieved by fixing the latent factor variances to 1.…”
Section: Fitted Modelsmentioning
confidence: 99%
“…First, given the poor performance of the ESEM/EFA models we increased the random starts for the rotation algorithm, from the software default of 30 to 1000. Past research has suggested that bi-factor rotations in ESEM/EFA are prone to local minima and that within these solutions, general factor variance is liable to be overstated (Mansolf & Reise, 2016). We used a sample size of n=200.…”
Section: Additional Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bifactor model's flexibility can also enable it to show superior global fit than alternatives, even when the other models were themselves used to simulate data (33,(38)(39)(40)(41)(42)(43)(44)(45)(46). For example, skewed item distributions and unmodeled cross-loadings or correlated residuals can all lead fit statistics to favor the bifactor model over a correlated-factors model (with no general factor), even if the correlatedfactors model more accurately describes the true structure (46,47).…”
Section: Biological Psychiatrymentioning
confidence: 99%